2020
DOI: 10.1101/2020.12.26.424423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The neutralization effect of Montelukast on SARS-CoV-2 is shown by multiscalein silicosimulations and combinedin vitrostudies

Abstract: Small molecule inhibitors have previously been investigated in different studies as possible therapeutics in the treatment of SARS-CoV-2. In the current drug repurposing study, we identified the leukotriene (D4) receptor antagonist Montelukast as a novel agent that simultaneously targets two important drug targets of SARS-CoV-2. We initially demonstrated the dual inhibition profile of Montelukast through multiscale molecular modeling studies. Next, we characterized its effect on both targets by different in vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In our current study, a pre-incubation of cells with the test compounds for 2 h prior to virus infection had a clear positive effect, suggesting a possible prophylactic role also for the petasins. While the montelukast IC 50 values were at 18.82 µM and 25 µM in in vitro cell culture models of SARS-CoV-2 activity [73,74], the IC 50 s for Ze 339, isopetasin and neopetasin determined in the current study were significantly lower. The visibly shallower inhibition curves of the petasin compounds compared to the antiviral mechanism of remdesivir could suggest a more complex mode of interference with the viral life cycle which is supported by the above mentioned various mechanisms of action of Ze 339.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In our current study, a pre-incubation of cells with the test compounds for 2 h prior to virus infection had a clear positive effect, suggesting a possible prophylactic role also for the petasins. While the montelukast IC 50 values were at 18.82 µM and 25 µM in in vitro cell culture models of SARS-CoV-2 activity [73,74], the IC 50 s for Ze 339, isopetasin and neopetasin determined in the current study were significantly lower. The visibly shallower inhibition curves of the petasin compounds compared to the antiviral mechanism of remdesivir could suggest a more complex mode of interference with the viral life cycle which is supported by the above mentioned various mechanisms of action of Ze 339.…”
Section: Discussionmentioning
confidence: 49%
“…It is further worth mentioning that the mechanism of anti-inflammatory action of Ze 339 is comparable to that of montelukast and zileuton, which are currently under discussion as therapeutic candidates for the treatment of COVID-19 [25][26][27][28][29]. In a recent study by Durdagi et al [73] demonstrated the neutralization effect of montelukast on SARS-CoV-2 in vitro by showing that virus replication could be significantly delayed. The authors suggested to consider montelukast for prophylactic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…24 In an insilico study, it has been shown that montelukast has anti-viral activity by interfering with the entry of the virus into the host cell. 25 Razi et al study shows that the immunostimulant given in atopy-negative children is effective. This suggests that EVW under 5 years old may be an immune defect that is insufficient to limit viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Caulerpin and monomethyl caulerpinate were docked into two different crystal structures of the SARS-CoV-2 spike protein receptor binding domain. 42 The study revealed that both compounds could interact with the pocket of the spike protein with which ACE2 also interacts and as such interfere with the binding of the latter (Fig. 3).…”
Section: Molecular Modelling Studiesmentioning
confidence: 97%